مشكلات تطبيق مدخل STEM بمدارس سلطنة عمان من وجهة نظر المعلمين - الرعمية، طفولة Alramiah, Tafoulah (جامعة طنطا - كلية التربية, 2022)
هدفت الدراسة إلى التعرف على مشكلات تطبيق مدخل STEM بمدراس سلطنة عمان من وجهة نظر المعلمين واشتملت عينة الدراسة على (56) معلم ومعلمة. في المدارس المطبقة لمدخل STEM وعددها 30 مدرسة تابعة لوزارة التربية والتعليم، واستخدمت الباحثة المنهج الوصفي كمنهج للدراسة، واستعانت بالاستبانة كأداة للدراسة، وقد توصلت الباحثة للعديد من النتائج أهمها إن مشكلات تطبيق مدخل STEM بمدراس سلطنة عمان من وجهة نظر المعلمين جاءت بدرجة موافقة (متوسطة)، وبمتوسط حسابي قدره (3.27)، وانحراف معياري (0.522)، وقد أوصت الدراسة عقد ندوات تعريفية ودورات تدريبية للمعلمين حول استخدام مدخل STEM، وتوفير الإمكانيات المادية والتقنية لتطبيق مدخل STEM. The study aimed to determine the problems of applying the STEM approach in schools in the Sultanate of Oman from the teachers' perspectives. The study sample included (56) male and female teachers from 30 schools used the STEM approach and affiliated with the Ministry of Education. The researcher used the descriptive method as a study approach and used the questionnaire as a study tool. The researcher concluded the problems of applying the STEM approach in schools in the Sultanate of Oman from the teachers’ perspectives came with (medium) approval, arithmetic mean (3.27), and a standard deviation (0.522). The study recommended conducting introductory seminars and training courses for teachers about using the STEM approach and providing the physical and technical potentials for applying the STEM approach.
Keywords: التعليم الأساسي -- استراتيجيات التدريس -- معلمو العلوم -- المؤسسات التعليمية -- سلطنة عمان